Evaluation of the Zachery Lystedt Law among female youth soccer players - O`Kane, J. W.; Levy, M. R.; Neradilek, M.; Polissar, N. L.; Schiff, M. A. (The Physician and Sportsmedicine, 2014)
Abstract: Background: Despite recent increased awareness about sports concussions, few studies have evaluated the effect of concussion laws on concussion outcomes among young athletes. The purpose of our study was to evaluate the effect of the Washington State Zachery Lystedt Concussion Law on playing with concussion symptoms and being evaluated by a health care provider. Methods: We performed a prospective cohort study of 351 elite female soccer players, aged 12 to 15 years, from 33 randomly selected youth soccer teams in the Puget Sound region of Washington State from 2008 to 2012. The Washington State Zachery Lystedt Concussion Law went into effect on July 1, 2009. Among concussed players (N = 59), we assessed the risk of playing with symptoms, the evaluation by a health care professional, and receiving a concussion diagnosis before and after the law was passed using logistic regression to estimate odds ratios and 95% CIs. Results: The majority of concussed players (59.3%) continued to play with symptoms, and we found no statistically significant difference in the proportion of players who played with symptoms before and after the law was passed. Only 44.1% of concussed players were evaluated by a health care provider, with no difference before and after the law was passed. Among those evaluated by a health care professional, players were 2.1-fold (95% CI, 1.0-10.1) more likely to receive a concussion diagnosis after the law was passed. Conclusion: The majority of concussed female youth soccer players report playing with symptoms. Legislation mandating concussion education and evaluation prior to returning to play was not associated with an increase in concussion evaluations by health care providers.